Trends of the Investment Fund Industry Development - Simanauskas, Leonas; Kucko, Irena (Ekonomika, 2004)
The research object of the present work is one of the elements of the financial system, the so-called alternative investment instrument - investment fund. The concept of investment fund is used here in the sense of publicly offered open-ended funds invested in transferable securities and money market funds, which refers to “mutual fund” in the US and UCITS’ in FEFSI’s2 statistics on the European investment funds industry. In Lithuania, the equivalent of investment fund is a variable capital investment company.Under the conditions produced by globalization when the spectrum of services and financial instruments is widening dramatically, competition between financial institutions is growing and mergers appear, the development of a financial system and its sensitivity to changes in global finance is an actual problem for Lithuania; as the financial system develops, the level of living and the average gross monthly earnings increase, the need for investing arises. The trends of the Lithuanian investment fund industry are analysed in relation to the European experience, that’s why the history and factors of development allocation of assets between different fund types of the European investment fund industry are examined.The purpose of this article is to examine the origin and rapid development of investment funds and to analyse trends of investment funds industry development.The methods used: analysis and generalization of scientific works and statistical data.